A Class of Organic Units Featuring Matrix‐Controlled Color‐Tunable Ultralong Organic Room Temperature Phosphorescence. Issue 3 (25th December 2022) - Zhang, Xue; Qian, Chen; Ma, Zhimin; Fu, Xiaohua; Li, Zewei; Jin, Huiwen; Chen, Mingxing; Jiang, Hong; Ma, Zhiyong
Abstract: A novel class of organic units (N‐1 and N‐2) and their derivatives (PNNA‐1 and PNNA‐2) with excellent property of ultralong organic room temperature phosphorescence (UORTP) is reported. In this work, N‐1, N‐2, and their derivatives function as the guests, while organic powders (PNCz, BBP, DBT) and polymethyl methacrylate (PMMA) serve as the host matrixes. Amazingly, the color of phosphorescence can be tuned in different states or by varying the host matrixes. At 77 K, all molecules show green afterglow in the monomer state but yellow afterglow in the aggregated state because strong intermolecular interactions exist in the self‐aggregate and induce a redshift of the afterglow. In particular, PNNA‐1 and PNNA‐2 demonstrate distinctive photoactivated green UORTP in the PMMA film owing to the generation of their cation radicals. Whereas the PNNA‐1@PNCz and PNNA‐2@PNCz doping powders give out yellow UORTP, showing matrix‐controlled color‐tunable UORTP. In PNCz, the cation radicals of PNNA‐1 and PNNA‐2 can stay stably and form strong intermolecular interactions with PNCz, leading to a redshift of ultralong phosphorescence. Abstract : Two organic units and their derivatives with tunable UORTP in defferent states or by varying doping matrixes are reported. PNNA‐1 and PNNA‐2 demonstrate distinctive photoactived green UORTP in PMMA films. The PNNA‐1@PNCz and PNNA‐2@PNCz doping systems emit yellow UORTP, showing matrix‐controlled color‐tunable UORTP.